PENGARUH TEKNIK CROSS LINE PADA HASIL BELAJAR MATEMATIKA MATERI PERKALIAN KELAS III SDN SUKOREJO - Cahyani, Welatika; Lestari, Wahyu Maulida (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2024)
Education can also be said as a process of acquiring knowledge, skills, and habits that will be inherited from one generation to the next. The learning outcomes are changes in someone who learns. Multiplication is also the mathematical operation of scaling one number with another. Multiplication is also repeated addition. The purpose of this study is to describe the effect of the crossline technique on the results of learning mathematics multiplication material for class III SDN Sukorejo. This type of research is a pre-experimental design type of one group pretest- posttest design. The subjects in this study were class III A students with a total of 25 students. The data collection technique used was a test sheet. based on the results of processing and analysis of the data collected in this study, namely the normality results obtained a value of p = 0.044 ≤ 0.05 in the pretest value and p value = 0.053 ≥ 0.05 in the posttest value. This shows that the pretest scores are not normally distributed and the posttest on student multiplication learning outcomes is normally distributed. Then the Wilcoxon test in this study obtained the value of Sig. (2-tailed) = 0.000. Because the sig value is 0.000 ≤ 0.05, it can be concluded that the hypothesis is accepted. Which means that the crossline technique has an effect on the results of learning mathematics multiplication material for class III SDN Sukorejo.